2017
DOI: 10.1177/0735633117715033
|View full text |Cite
|
Sign up to set email alerts
|

Student Perspectives on the Flipped-Classroom Approach and Collaborative Problem-Solving Process

Abstract: The flipped-classroom approach has gained increasing popularity and interest in engineering education. The purpose of this study was to investigate (a) student perspectives on the flipped-classroom approach in a transportation-engineering course and (b) how students used the in-class time dedicated to collaborative problem solving. To this end, the study adopted a mixed-methods approach. Quantitative data included an end-ofsemester survey and student course grades. Qualitative data included information from fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Thus, it was observed that the success of the action step designed by FL in solving the research problem was supported by theoretical foundations in addition to the present study data. Reference [45] has revealed that students who are studying engineering are satisfied with being in a flexible and modern educational environment, they spend more quality time with their teachers and they have the opportunity to work in solving the problem in cooperation with their friends.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it was observed that the success of the action step designed by FL in solving the research problem was supported by theoretical foundations in addition to the present study data. Reference [45] has revealed that students who are studying engineering are satisfied with being in a flexible and modern educational environment, they spend more quality time with their teachers and they have the opportunity to work in solving the problem in cooperation with their friends.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…With this method, students are provided with several opportunities such as controlling the learning time based on their own learning speed, playing a more interactive and active role in the classroom, and applied learning [37,40,63]. In addition, many studies in the literature reveal that inverted learning is effective in students' learning [19,45,82], although a few studies on FL have shown that the effect is low [6,51] or with no effect [16]. It can be said that the studies on FL have started to increase in recent years with the existence of studies that have shown that the effect of FL on learning is positive.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Hence, flipped classrooms is likely to directly and positively affect students' knowledge. Additionally, Love et al [17] pointed out that students in this active learning context develop a higher level of ability to work in groups [18] and help students to improve their ability to learn on their own [19]. This implies that flipped classrooms is likely to enhance students' abilities and skills, and directly and positively affect students' skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The pedagogy used in engineering education must enhance the technical skills measured in terms of improved academic performance 1618 and professional skills such as: (1) ability to work in a group 19,20 exhibiting excellent communication skills 21,22 and critical thinking that enables to think out of box and provide solution differently. 4,19 Also the teaching pedagogy must address to reduce the high attrition rate 23,24 and retain students to graduate their discipline 25,26 with competencies meeting the industry requirements.…”
Section: Introductionmentioning
confidence: 99%